Predicting Recidivism for Acquired Cholesteatoma: Evaluation of a Current Staging System. Issue 10 (December 2020) - Angeli, Simon; Shahal, David; Brown, Clifford Scott; Herman, Bjorn
Abstract : Objective: Assess the utility and prognostic capabilities of the European Academy of Otology and Neurotology (EAONO) and Japanese Otological Society (JOS) cholesteatoma classification system, specifically for retraction pocket cholesteatoma. Study Design: Retrospective. Setting: Tertiary referral hospital. Patients: Adults and children with retraction pocket cholesteatoma. Interventions: Primary and planned second-look tympanoplasty with mastoidectomy. Main Outcome Measures: Incidence of recurrent or residual cholesteatoma at planned second-look surgery. Independent variables of age, gender, size of canal defect, and mucosa status were assessed. Additionally, the cholesteatoma classification, stage, and extent according to the EAONO/JOS system were recorded during the primary surgery. Results: A total of 125 cases were included. Twelve (9.6%) cases had recidivism over an average time of 7.5 months: the recurrence rate was 4% (n = 5), residual rate was 5% (n = 6), and one patient had both recurrent and residual disease (0.8%). Residual cholesteatoma occurred more frequently in children ( p  = 0.04, RR = 7.9 [1.0, 63.6]). Supratubal recess (S1) disease was associated with both recurrent cholesteatoma ( p  = 0.04, RR = 5.9 [1.3, 27.2]) and recidivism ( p  = 0.01, RR = 4.2 [1.5, 11.9]). Larger canal defects also showed an association with residual disease ( p  = 0.017). Conclusion: Younger patients and those with large ear canal defects tend to have residual disease at second-look surgery. Supratubal recess disease is also associated with recurrence. Despite the utility of the EAONO/JOS classification and staging system for cholesteatoma description and type, the prognostic value remains uncertain.